1983
DOI: 10.1037/0022-006x.51.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Symptom Checklist-90 with acute psychiatric inpatients.

Abstract: Acute psychiatric inpatients (N = 451) in a state hospital were given the Symptom Checklist-90 (SCL-90) as part of the routine admission procedures. Previous factor analytic research with the SCL-90 had focused primarily on outpatients. Principal component factor analysis resulted in nine factors that differ somewhat from factors found in previous research with psychiatric outpatients. Eight of the nine factors were found to be reliable using coefficient alpha. Explanations for differences in factor structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
40
1

Year Published

1986
1986
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 5 publications
9
40
1
Order By: Relevance
“…Sleep Disturbance, and the factor De pression was given greater weight. The impos sibility to reproduce the factor 'anxiety' is a confirmation of the results of other studies [Hoffmann and Overall, 1978;Clark and Friedman, 1983;Holcomb et al, 1983], The proposed new factorial structure allowed a better discrimination between the three groups of patients with dysthymia. anxiety disorders and anorexia nervosa.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Sleep Disturbance, and the factor De pression was given greater weight. The impos sibility to reproduce the factor 'anxiety' is a confirmation of the results of other studies [Hoffmann and Overall, 1978;Clark and Friedman, 1983;Holcomb et al, 1983], The proposed new factorial structure allowed a better discrimination between the three groups of patients with dysthymia. anxiety disorders and anorexia nervosa.…”
Section: Discussionsupporting
confidence: 69%
“…Earlier studies sug gested a revision of the factors paranoid idea tion. psychoticism, anxiety [Angst et al, 1984;Hoffmann and Overall, 1978;Clark and Friedman, 1983;Holcomb et al, 1983], A PCA allocated the items to factors which were considerably less interdependent than in the original version. Despite the fact that our sample was clinical and the sample of Angst et al [1984] was nonclinical, we also found changes in the factor Paranoid Ideation and Psychoticism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a report published after the present study was in progress, Holcomb et al (1983) factor analyzed SCL-90 responses from a sample of state hospital inpatients. Neither an Interpersonal Sensitivity factor nor a Functional Impairment factor was identified, although their nine-factor solution did include the Depression, Somatization, Phobic Anxiety, and Hostility factors (Holcomb et al, 1983).…”
mentioning
confidence: 99%